Technical and economic feasibility of the use of airships within two Portuguese market niches: the tourism and the urban logistic case studies - Rafael Santos; Jorge Silva (European Regional Science Association (ERSA), 2012)
All over the world there are several countries where airships are being used for military and civilian purposes. The rebirth of this mean of transportation, capable of easily overcoming some deficiencies of the conventional ones, brings medium and long term economic benefits. In addition, they offer different services at lower costs, and they also may stimulate new commercial and industrial activities and even new transactional routes. The background of airship technology comes from the XVIII century. Since then, all those years were of scientific and empirical knowledge. Now, they form the basis for a sustainable future in emerging technologies, making the return of airships possible. This revived interest in airship technology brings a multitude of technical concepts resulting from interdisciplinary research. Consequently, the state of art of airships presents new research which paves the way for the reappearance of renewed horizons with regards to the use of airships. Companies are focused on the research, development and testing of new airship concepts and designs too. Nowadays, airships are being studied for commercial transport in different parts of the globe, from Canada, Brazil, Peru, to Australia. India, for example, has studies about the connection to remote areas with poor surface infrastructure which only can be reached by air or walking. This way, it's expected that airships will become a competitive mean of transport to link areas served by deficient transport infrastructures. Taking the principles of sustainable development of air transport, airships are the most environment-friendly vehicles with lower fuel consumption and with higher endurance. Therefore, as a result, they are paving the way for new markets. This work examines these technological improvements and the economic feasibility of the use of airships in certain market niches. Mainly, this work makes use of a study concerning the viability of the use of airships within Portuguese Tourism and Urban Logistic activity sectors. This paper is organized as follows: firstly, state of the art reviews about airships technological characteristics: operational constraints, operation scenarios, and international and national legislation. Secondly, improvement of two case studies within the Portuguese territory (touristic flights and urban logistic activity): operational parameters evaluation and operating cost estimation. And thirdly, some insights and challenges of research that is still in progress.
Keywords: L93; O18; R11; 330; Airships; Technical and Economic Feasibility; Market Niches; Tourism; Urban Logistics